Board of Directors’ Responsibility in The Implementation of Know Your Customer (Kyc) in The Case of Default by Debtors (CASE STUDY NO. 266/PDT.G/2012/PN. SBY) - Syahir, Fabhian Halky; Satino , Satino (Riviera Publishing, 2025)
The suboptimal implementation of Know Your Customer (KYC) by bank directors contributes to the increase in non-performing loans (NPLs). This normative legal research analyzes the legal responsibility of directors for the failure to implement KYC in the context of debtor default, as well as the integration of KYC in creditworthiness analysis (5C). The results show that KYC has evolved into a fundamental instrument of the board of directors' duty of care, which is functionally integrated to validate the Condition and Collateral criteria. Analysis of Decision No. 266/Pdt.G/2012/PN. SBY indicates that KYC failure constitutes a breach of fiduciary duty that has a causal relationship with the bank's losses. This negligence opens up multidimensional liability for directors, including administrative sanctions, civil lawsuits (Article 1365 of the Civil Code), and potential criminal liability (TPPU). The board of directors holds full responsibility to ensure the effectiveness of KYC as a key pillar of Good Corporate Governance (GCG) to mitigate credit and legal risks.